The Efficacy of Topical Vitamin C and Microneedling for Photoaging - Pratiwi, Karina Dyahtantri; Listiawan, Muhammad Yulianto; Ervianti, Evy; Damayanti, Damayanti; Hendradi, Esti; Prakoeswa, Cita Rosita Sigit; Sawitri, Sawitri (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Photoaging is premature skin aging caused by exposure to ultraviolet (UV) radiation. Vitamin C is an antioxidant that inhibits the tyrosinase enzyme that can reduce pigmentation. Microneedling procedure can improve the penetration of topical vitamin C, and it has skin rejuvenating effects to reduce wrinkles and minimize pore size. Purpose: The main purpose of this study was to evaluate the efficacy of topical vitamin C application after microneedling intervention for the clinical improvement of photoaging. Methods: Twenty-four women with photoaged skin participated in this randomization study, and they were divided into control and intervention groups. Solution of 0.9% NaCl and microneedling were performed to control group, and topical vitamin C and microneedling were performed to intervention group. Three intervention sessions were repeated at a 2 week interval. Signs of photoaging such as pigmentation, wrinkles, and pores were evaluated using Metis DBQ3-1, and the data were obtained numerically. Result: The data analysis revealed a significant improvement in pigmentation in the intervention group compared to control group (p<0.05). Wrinkles and pores evaluation revealed no significant difference between the control and intervention groups. Conclusion: Topical vitamin C after microneedling procedure has provided a significant improvement in pigmentation compared to NaCl 0.9% after microneedling.